Ochrona zrównoważonego rozwoju oraz ładu przestrzennego w procesie budowlanym - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Ensuring sustainable development and spatial order is the principle of the planning law. The local development plan and the decision on the conditions for construction and land development shall be consistent with this principle. This principle limits the ownership right. This right is the source of construction freedom. Construction freedom is limited inter alia by the planning law. The participants in the construction process and the authorities of the architectural and construction administration shall ensure compliance of the construction process with the local development plan and the decision on the conditions for construction and land development. The construction work, the maintenance of building structures and the legalization of the unauthorized construction shall be consistent with those acts.
Keywords: miejscowy plan zagospodarowania przestrzennego; decyzja o warunkach zabudowy i zagospodarowania terenu; swoboda zabudowy; inwestor